Hawking radiation from Elko particles tunnelling across black-strings horizon - Rocha, R. da; Hoff da Silva, Julio Marny [UNESP] (Epl Association, European Physical Society, 2014)
We apply the tunnelling method for the emission and absorption of Elko particles in the event horizon of a black-string solution. We show that Elko particles are emitted at the expected Hawking temperature from black strings, but with a quite different signature with respect to the Dirac particles. We employ the Hamilton-Jacobi technique to black-hole tunnelling, by applying the WKB approximation to the coupled system of Dirac-like equations governing the Elko particle dynamics. As a typical signature, different Elko particles are shown to produce the same standard Hawking temperature for black strings. However, we prove that they present the same probability irrespectively of outgoing or ingoing the black-hole horizon. This provides a typical signature for mass-dimension-one fermions, that is different from the mass-dimension-three halves fermions inherent to Dirac particles, as different Dirac spinor fields have distinct inward and outward probability of tunnelling. Copyright (C) EPLA, 2014